Psychological Ownership in Marketing: - Saori Kanno (Maketingu Janaru, 2023)
In recent years, the concept of psychological ownership has garnered significant attention in marketing. Psychological ownership refers to the sense of ownership that individuals feel towards an object and the feeling that the object is “mine.” With the rise of digitalization and the sharing economy, consumers’ consumption patterns have expanded to include immaterial and sharing goods. Psychological ownership has emerged as a crucial concept for understanding the increasingly complex relationship between consumers and objects. This paper reviews 48 recent articles published in leading academic journals in the marketing field to analyze the latest trends in research on psychological ownership in marketing. The aim is to gain insights into the current status of research on psychological ownership and identify future directions for exploration.